2022
DOI: 10.34190/ejel.20.4.2262
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Learners’ Sex and STEM/non-STEM Majors on Remote Learning: A National Study of Undergraduates in Qatar

Abstract: The sudden and prolonged disruption to learning caused by the COVID-19 pandemic has exposed the vulnerabilities of traditional higher education and revealed the need for a rapid transformation. Lessons from the pandemic have made it clear that the future of higher education will rely heavily on e-learning and the agility of institutions to seamlessly transition between face-to-face, blended/hybrid, and fully online learning. As institutions begin their post-pandemic planning, the online experiences of differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In relation, Newsome et al (2022) concluded that in terms of in instructor behavior, assessment and evaluation, and tools and technologies, male students have more positive perception than females. During the pandemic, adolescent girls than boys showed greater negative impacts in both well-being and behavioral change that is linked to decreased communication with peers and family members through phone or social media (Halldorsdottir et al, (2021).…”
Section: Resultsmentioning
confidence: 99%
“…In relation, Newsome et al (2022) concluded that in terms of in instructor behavior, assessment and evaluation, and tools and technologies, male students have more positive perception than females. During the pandemic, adolescent girls than boys showed greater negative impacts in both well-being and behavioral change that is linked to decreased communication with peers and family members through phone or social media (Halldorsdottir et al, (2021).…”
Section: Resultsmentioning
confidence: 99%
“…The distribution was 84.3% females and 15.7% males at the individual level. This female majority proportion is a good representation of the undergraduate population in Qatar since, according to the Qatar Planning and Statistics Authority, 2019, Qatar has a similar undergraduate proportion (Newsome et al, 2022). In terms of ethnicity, 68% identified as non-Qataris and 32% as Qataris, which is also a close representation of the population in Qatar (Liloia, 2019).…”
Section: Participantsmentioning
confidence: 90%
“…The simplicity of human-computer interaction, incomplete learning data, and the lack of practical aspects are also more prominent (Carrillo & Flores, 2020). The results of a study showed that in distance learning students' satisfaction with the tools, assessments, and course design had the greatest impact on overall course satisfaction (Newsome, et al, 2022).…”
Section: Literature Review Relevant Theorymentioning
confidence: 99%